Analisis Pengaruh Harga, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Batik Danar Hadi Surakarta - Nugroho, Rachmad Tri, Dr. Edi Purwo Saputro, S.E., M.Si (2016)
This research was conducted in Danar Hadi Batik Surakarta, which aims to analyze the effect of the Purchase Price to the Decision, to analyze the effect of promotion to the purchase decision. Analyze the effects of Product Quality to the purchase decision. This study uses the survey design, the research took samples from a population and using questionnaires. The samples used were 100 students at the University of Muhammadiyah Surakarta. Methods of data collection in this study used a questionnaire to students. The analytical tool used in the research is to test the instrument, the classical assumption test, data analysis (Multiple Linear Regression Analysis, t-test, F and coefficient of determination (R ²). The results of data analysis can be obtained are positively influence price and significant impact on purchase decision Danarhadi Batik Surakarta, influences of the Promotion positively and significantly to the Purchase Decision Danarhadi Batik Surakarta and influences of the Purchase Decision Product Quality Danarhadi Batik Surakarta. There is the influence of price, promotion and product quality simultaneously to Purchase Decision Danarhadi Batik Surakarta. Keywords: Price, Promotion, Product Quality, Purchasing Decisions